Synthesis of Al2O3 + хFe-based thermocrystals; Bulletin of the Russian Academy of Sciences: Physics; Vol. 81, iss. 12 - Karban O. V. Oksana Vladislavovna; Salamatov E. I. Evgeny Ivanovich; Konygin G. N. Grigory Nikolaevich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Muhgalin V. V. Vladislav Viktorovich; Radygina A. V. (2017, 2017)
Title screen